Times Higher Education World University Rankings for 2012—2013 and Prospects of Science Development in Armenia - Haroutiunian, T. (Наука та інновації, 2014)
The article covers Times Higher Education World Universities Rankings and the criteria, according to which these universities are chosen. Most of them are in North America and Europe and represent Anglo-Saxon school, In the list of top universities appears more and more technical and natural science Asian universities as a result of increasing the number of research universities. The possibility of establishing a research university in Armenia, as well as circumstances that can promote or impede it are considered. The megaprojects implemented in Armenia are presented and the role of research universities in the promotion and establishment of these projects is substantiated. У даній статті наведено список кращих університетів,
представлений журналом Tіmes Hіgher Educatіon, а також розглядаються критерії, за якими вони вибираються. Більшість цих університетів знаходиться в Північній
Америці і Європі, значна частина з них — представники
англо-саксонської школи. У списку кращих університетів з’являється все більше азійських технічних й природничо-наукових вузів, що є наслідком збільшення числа
дослідницьких університетів. Розглянуті можливість створення у Вірменії дослідницького університету, а також
обставини, які можуть цьому сприяти або перешкоджати. Розглядаються мегапроекти й обґрунтовується роль
дослідницьких університетів у просуванні й становленні цих проектів у Вірменії. В данной статье приведен список лучших университетов, представленный журналом Times Higher Education, а
также рассматриваются критерии, по которым они выбираются. Большинство этих университетов находится в Северной Америке и Европе, значительная часть из них —
представители англо-саксонской школы. В списке лучших университетов появляется все больше азиатских
технических и естественно-научных вузов, что является
следствием увеличения числа исследовательских университетов. Рассмотрены возможность создания в Армении исследовательского университета, а также обстоятельства, которые могут этому способствовать или препятствовать. Рассматриваются мегапроекты и обосновывается роль исследовательских университетов в продвижении и становлении этих проектов в Армении.